Sustainable urban development strategies to enhance outdoor thermal comfort and promote walkability in the United Arab Emirates - ALTENEIJI, AHMED SALIM AHMED SAIF (2021)
Thermal comfort has a variety of implications for how people act in their built environment, including their mobility options. In many places, particularly those prone to severe weather, trip time and distance are less significant than the outside thermal. Accordingly, Outdoor comfort is necessary when it comes to encouraging individuals to walk, bike, or take any other form of sustainable transportation. The thesis argues that there is lack of a wider framework that evaluates numerous design iterations in terms of comfort and walkability at the same time is mostly due to a lack of adequate connectivity between the two concepts. As such, the fundamental goal of this research is to create a link between outdoor thermal comfort and walkability by examining how various sustainable design options for increasing outdoor thermal comfort may be codified to also increase walkability. The methodology used in this study can address both the quantitative and qualitative aspects of the problem while also allowing for the examination of several design iterations. The research used an integrated methodology that combined field survey and simulation, allowing the researcher to analyse the topic holistically and critically while studying each parameter in its own context. Field survey was employed in this research to better understand people's behaviour under various conditions, while simulation gave a complete control for the researcher to analyse the research problem parametrically. The study assessed people's thermal perception and level of comfort through a field survey and a thermal walk experiment. The effect of urban morphology on street orientation and H/W aspect ratio is then investigated parametrically utilizing the Rhino/Grasshopper interface in conjunction with the ladybug tools plugin. According to the findings of the field investigation, pedestrians in the UAE are most comfortable when the outdoor air temperature is between 25 and 30 degrees. While the thermal walk experiment demonstrated that going outdoors in the summer can raise the skin's temperature by up to two degrees. Moreover, individuals can walk less than 10 min in summertime before the feel very uncomfortable. while this duration significantly increases if the street is shaded. The result if simulations shows that street orientation and H/W aspect ratio can contribute to enhancement of 2 °C. In the case study NW-SE street orientation achieved the best result and the current H/W aspect ratio which is around 4.2.